Online health information seeking among patients attending primary care clinics in Bahrain: a cross-sectional study - Ali, Aqeela A.; AliFardan, Fatema A.; Aljamri, Sahar Z.; Salman, Wadeea M.; Mandeel, Mohamed A.; Bahram, Samya (International Journal of Research in Medical Sciences, 2022)
Background: Online health information seeking is prevalent among patients nowadays and this might influence the medical consultation outcome and affect the patient-doctor relationship. Objective was to determine the prevalence of online health information seeking behavior among primary care clinics attendees in Bahrain and the impact on patient-doctor relationship. Methods: Patients attending primary care clinics in Bahrain were asked to complete a previously adapted self-administered questionnaire that studied demographical data, frequency of online use in general and for health-related information and pattern of online health information seeking including reasons searched for and sources used. The logistic regression analysis done to explore respondent’s characteristics with health seeking behavior online. Results: Ninety-seven percent (97%) of the study population used the internet and (94.7%) had searched for online health information. The two main types of information sought were disease-related information (88.7%) and complementary and alternative medicine (55%). Fifty-three percent used reliable sources (i.e., Ministry of Health (43.3%), hospital websites (14.9%), medical encyclopedias (e.g., PubMed and Medline plus) (17.4%). Approximately (39.3%) use social networks to find information (including Facebook and Twitter). Convenience and usability were the main reasons (88.9%). Fifty-five percent (55%) asked or shared health information they found online with their doctor. Conclusions: Online health information seeking is highly prevalent in Bahrain among primary care clinic attendees. Sources were chosen mainly for their convenience, availability and being easily understood. A good number shared health information found online with their physicians. Physicians should be aware about patients’ online health seeking behavior and address that during consultation.